US patent no. 7,343,253 B2: Coriolis mode processing - Henry, M (United States Patent and Trademark Office, 2008)
Flowmeters are described in which a sensor signal received from a sensor that is attached to vibratable flowtube, so as to determine properties of a fluid within the flowtube, contains a drive signal component and a coriolis mode component. The flowmeters are operable to determine drive parameters of the drive signal component, as well as coriolis parameters of the coriolis mode component. By analyzing the sensor signal based on the drive signal parameters, and not on the coriolis signal parameters, the flowmeters are able to provide stable and accurate determinations of the properties of the fluid.